Hyperprogressive disease during PD-1 blockade in patients with advanced pancreatic cancer - Shiyun Chen; Lu Han; Shiyuan Guo; Zhaoli Tan; Guanghai Dai (Taylor & Francis Group, 2023)
The occurrence of markedly accelerated tumor growth during immunotherapy is considered a new mode of progression called hyperprogressive disease (HPD) and its impact on pancreatic cancer (PC) patients receiving immunotherapy is unknown. In this study, we described and explored the incidence, prognosis and predictors of HPD in patients with advanced PC treated with programmed cell death-1 (PD-1) inhibitors. We retrospectively analyzed clinicopathological data from 104 patients with advanced pancreatic cancer who were treated with PD-1 inhibitors at our institution during 2015-2020 and identified 10 (9.6%) patients with HPD. Overall survival (OS) was significantly poorer in patients with HPD compared to patients with progressive disease (PD) (median OS: 5.6 vs. 3.6 months, p < .01). Clinicopathological factors associated with the occurrence of HPD included smoking, metastatic sites >2, liver metastasis, antibiotic therapy within 21 days before immunotherapy (Abx B21), hemoglobin (Hb) level <110 g/L, and PD-1 inhibitor treatment line >2. Subgroup analysis showed that high levels of CA19-9 at baseline were associated with the development of subsequent HPD (p = .024) and a worse prognosis (mOS:16.2 months vs. 6.1 months, p < .01). Our study demonstrated that HPD may occur in PC patients treated with PD-1 inhibitors and is associated with several clinicopathological characteristics and poor prognosis. The baseline tumor marker CA19-9 may be one of the early predictors of HPD development in PC patients receiving immunotherapy.